2021
DOI: 10.1002/fsn3.2624
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium chloride and pH on soluble complex of whey protein‐basil seed gum and xanthan gum

Abstract: Summary Interaction between biopolymers generates different rheological behaviors, which can be effective on the structure of food products. One way to control the polysaccharide–protein interaction is the variation of acidic and ionic strength. In this research, the different amounts of pHs (3–7) and calcium chloride (5–20 mM) were investigated on a soluble complex of whey protein concentrate (WPC) with xanthan gum (XG) and basil seed gum (BSG). The complex characteristic was investigated according to turbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…From all of the formulations for both HM and LM pectin, the graph first showed the viscosity was at its highest point, and then it decreased and continued stably which shows shear-thinning behaviour in all complexes. This result is consistent with the study by Sarraf et al (2021), which found that the rheological properties of hydrocolloids were influenced by pH and salt concentration. In these cases, the polymer molecule chains are arbitrarily positioned when the sample solutions are at rest, but are aligned in the same flow direction when shear forces are applied.…”
Section: Viscoelastic Properties Of the Food Inksupporting
confidence: 93%
“…From all of the formulations for both HM and LM pectin, the graph first showed the viscosity was at its highest point, and then it decreased and continued stably which shows shear-thinning behaviour in all complexes. This result is consistent with the study by Sarraf et al (2021), which found that the rheological properties of hydrocolloids were influenced by pH and salt concentration. In these cases, the polymer molecule chains are arbitrarily positioned when the sample solutions are at rest, but are aligned in the same flow direction when shear forces are applied.…”
Section: Viscoelastic Properties Of the Food Inksupporting
confidence: 93%
“…It also seems that the amount of acid strength is also very effective on berberine release. The zeta potential of WPC emulsion gel is −22.40 mV according to previous study and changes to the more negative value with the increase of anionic polysaccharides on the surface of the particles, so that the zeta potential of 0.6BSG:WPC and 0.6 XG:WPC emulsion gels are −28.50 and −26 mV, respectively (Sarraf et al., 2023).…”
Section: Resultsmentioning
confidence: 77%
“…The lower strength of the oleogel containing WPC compared to the other oleogels, indicates that polysaccharides played an effective role on the increasing strength of oleogel structures and controlling the release of berberine. According to the results of texture analysis on their primary emulsion gels and oleogles, hardness, consistency of the structure were raised of in line with increasing the concentration of polysaccharides, this event was not far from expected (Sarraf et al., 2023). It also seems that the amount of acid strength is also very effective on berberine release.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The final way is to add a stabilizer, which is an environmentally friendly and simple. For example, polysaccharides can be used as stabilizers of WPI by forming protein-polysaccharide complexes [9,16], which can improve the emulsion stability of WPI and polysaccharides, such as Tremella fuciformis polysaccharide [12], xanthan gum (XG) [17], and pectin [18].…”
Section: Introductionmentioning
confidence: 99%